Comparison of the Index of Nutritional Quality in Breast Cancer Patients With Healthy Women - Behrad Nasab, Mojgan; Afsharfar, Maryam; Ahmadzadeh, Mina; Vahid, Farhad; Gholamalizadeh, Maryam; Abbastorki, Saheb; Davoodi, Sayed Hossein; Majidi, Nazanin; Akbari, Mohammad Esmail; Doaei, Saeid (Frontiers in Nutrition, 2022)
Background: The index of nutritional quality is derived from food frequency questionnaire (FFQ) and is a method of quantitative and qualitative analysis of diet. This study aimed to compare the index of nutritional quality (INQ) for different dietary components between breast cancer patients and healthy control. Methods: This case-control study was performed on 180 women with BC and 360 healthy women. Data on general characteristics, medical history, anthropometric indices, physical activity, alcohol consumption, reproductive history, smoking, and dietary intake were collected. A valid FFQ was used to assess the intake of nutrients and the INQ was calculated based on the daily intake of the nutrients. Results: There were was a significant association between BC and INQ of vitamin A (OR=0.07, 0.01-0.29), vitamin E (OR=0.43, 0.20-0.93), vitamin B6 (OR=0.003, 0.000-0.021), riboflavin (OR=0.25, 0.11-0.59), vitamin K (OR=0.58, 0.37-0.90), biotin (OR=0.07, 0.02-0.26), vitamin B12 (OR= 0.32, 0.18-0.56), vitamin C (OR=0.72, 0.55-0.95), zinc (OR=0.020, 0.005-0.083), calcium (OR=0.14, 0.04-0.54) and magnesium (OR=0.003, 0.000-0.024). Further adjustment for BMI disappeared the association between INQ of vitamin C and BC. The results did not change after further adjustments for waist circumstance and total calorie intake Conclusion: A significant association was observed between BC and INQ of some micronutrients. INQ can be used as an indicator in assessing clinical nutrition-related problems. Future longitudinal studies are needed to confirm these results.